Strategi Komunikasi Transformasional dalam Membangun Loyalitas dan Motivasi Kerja: Analisis pada PT Asam Jawa - Dwi Ulina Sari; Exsan Adde; Mauly Arzak Julika (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the implementation of transformational leadership communication styles at PT Asam Jawa and identify the challenges that arise within a family-based organizational culture. Using a descriptive qualitative method with a case study approach, data were collected through in-depth interviews with the General Manager and four employees from various divisions. The results indicate that the leadership has implemented transformational leadership dimensions through idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. This has proven effective in increasing employee motivation and performance through an emotional vision and tangible rewards. However, significant challenges emerged, specifically professional communication barriers caused by a sense of hesitation (ga enakan) and potential social jealousy between divisions triggered by the strong family-based system. In conclusion, while the transformational style functions well, adjustments in communication strategies are needed to balance family values with professional firmness. This study recommends strengthening intrinsic motivation to reduce dependence on external stimuli for long-term organizational productivity.